2019
DOI: 10.1177/0093854819891457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Mindfulness-Based Interventions in Incarcerated Populations: A Meta-Analysis

Abstract: A growing body of research supports the use of mindfulness-based interventions (MBIs) in incarcerated populations; however, treatment effectiveness remains unclear. This meta-analysis of 22 studies ( N = 2,265, 75% male) quantified the effectiveness of MBIs in incarcerated populations on key psychological outcomes and criminogenic needs. Results from pre–post studies indicated MBIs had a small to moderate effect on all outcomes, but this was not supported by controlled studies. Studies with older participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 73 publications
0
22
1
1
Order By: Relevance
“…There has been evidence of increased mindfulness through mindfulness-based interventions in prison and psychiatric populations ( 8 , 28 ). For forensic inpatients, prior research has demonstrated an increasing trend in the observing facet in their study on mindful-yoga training with forensic inpatients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been evidence of increased mindfulness through mindfulness-based interventions in prison and psychiatric populations ( 8 , 28 ). For forensic inpatients, prior research has demonstrated an increasing trend in the observing facet in their study on mindful-yoga training with forensic inpatients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers of incarcerated populations have noted prison is a stressful environment ( 2 ), and the present investigation found a significant decrease in perceived stress from baseline to post-intervention, but not at follow-up. While quantitative and qualitative studies examining the impact of mindfulness and/or yoga on stress have shown significant reductions in prison populations [e.g., ( 28 )] and in psychiatric inpatients [e.g., ( 46 )], others have not found reductions in perceived stress [e.g., ( 34 )]. Interestingly, although Sistig et al ( 34 ) did not have significant quantitative findings, the forensic inpatients qualitatively reported mindful-yoga training aided in stress management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This information would help with the development of interventions that are culturally tailored and effective. In a meta-analysis of mindfulness-based interventions (MBIs) with incarcerated adults, findings offered preliminary support of the efficacy of MBIs in targeting psychological health in incarcerated populations (Per et al, 2020). Further controlled studies are required to examine criminogenic outcomes and recidivism rates after treatment, especially for youth and girls of color.…”
Section: Limitations and Implicationsmentioning
confidence: 99%